Genitalic stridulation during copulation in a species of crane fly, Tipula (Bellardina) sp. (Diptera: Tipulidae) - Eberhard, William G (2009)
The male genitalia of many animal groups have elaborate and species-specific forms. One hypothesis to explain why this is so is that male genitalia function as stimulatory devices that are under sexual selection by cryptic female choice. This report is based on a videotaped observation of a single male of an unidentified species of Tipula (Bellarina) from San José Province, Costa Rica. A male crane fly stridulated (produced vibrations) during copulation using sustained and stereotyped movements of file and scraper structures on his genitalia. Males of related species have similar file and scraper structures on their genitalia, suggesting that they probably also stridulate during copulation.